2005
DOI: 10.1038/sj.bjp.0706112
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of granuloma‐associated angiogenesis by controlling mast cell mediator release: role of mast cell protease‐5

Abstract: 1 We investigated the role of mast cells in granuloma-associated angiogenesis in rat by using: (i) a mast cell membrane stabilizer, ketotifen; (ii) a mast cell depleting agent, compound 48/80. Moreover, we focused on the role of chymases, which exhibit proinflammatory and proangiogenic properties by using: (i) chymostatin, an inhibitor of chymase activity; (ii) a specific antisense oligonucleotide (AS-ODN) designed against rat mast cell protease-5 (rMCP-5), the most abundantly expressed chymase in the skin. 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…Animal studies have shown that neovascularization is reduced in MC-deficient mice, and granuloma-associated neovascularization can be inhibited by controlling MC activation. 27 MC-derived histamine upregulates c-jun expression and c-jun N-terminal kinase (JNK) activity, 28 and increased JNK activity seems to promote aneurysm formation. 29 In addition, MCs may promote chemotaxis of inflammatory cells into the AAA wall by inducing ET-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that neovascularization is reduced in MC-deficient mice, and granuloma-associated neovascularization can be inhibited by controlling MC activation. 27 MC-derived histamine upregulates c-jun expression and c-jun N-terminal kinase (JNK) activity, 28 and increased JNK activity seems to promote aneurysm formation. 29 In addition, MCs may promote chemotaxis of inflammatory cells into the AAA wall by inducing ET-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5]11,12 It has also been shown to stimulate plasma cell production and induce angiogenesis and, therefore, remodeling within 7 days of an injury occurring. 27,28 Accordingly, myrrh may be potentially useful in the induction of wound healing and repair.…”
Section: 28mentioning
confidence: 99%
“…To determine the qualitative capacity of the newly formed tumor vessels to supply the respective tissue with oxygen and nutrients, the amount of hemoglobin was determined in tumors with and without hGBP-1 expression ( Figure 5B). This well-established method is applied to quantify the actual state of perfusion within a given tumor tissue (34,35). For each group of tumors, 18 samples were analyzed.…”
Section: Reduced Tumor Growth Corresponds With Decreased Hemoglobin Cmentioning
confidence: 99%